O coro em O díscolo de Menandro - Dezotti, Maria Celeste Consolin [UNESP] (My University, 2010)
There is a consensus among scholars that the chorus in Menander’s time had become totally detached from stage-action; its performances, marked in the Greek text by the word ΧΟΡΟΥ, separated like interludes the acts from each other within the plays; the chorus had a technical function: provide a break in the action to cover certain off-stage events and indicate the passing of time. This paper, however, examines in Dyskolos, one of Menander’s early comedies, the relation between the chorus and Cnemon present in the old man’s words that makes generalizations about human relationships, and shows that in this comedy the chorus of the followers of the god Pan was exploited by the poet as a source of achieving various dramatic effects.
Keywords: Teatro grego; Espetáculo; Coro; Menandro; O Díscolo